ANALISA KERUSAKAN POMPA OLI TEMPERATURE CONTROL UNIT PADA MESIN LONGITUDINAL STRECHER DITINJAU DARI KERUGIAN BIAYA PRODUKSI DI PT. POLIDAYAGUNA PERKASA UNGARAN : ANALISA KERUSAKAN POMPA OLI TEMPERATURE CONTROL UNIT PADA MESIN LONGITUDINAL STRECHER DITINJAU DARI KERUGIAN BIAYA PRODUKSI DI PT. POLIDAYAGUNA PERKASA UNGARAN - Muhammad, Rouf; Safi'i, Muhammad; Baiti Jannati, Nur (Yayasan Literasi Sains Indonesia, 2024)
A pump is a machine that functions to move fluids by converting mechanical energy into fluid energy and pressure, transporting fluids through a piping system. Head, flow, efficiency, performance and performance are the main concerns for centrifugal pumps, these aspects can be used as benchmarks in choosing the type of pump that suits your needs. Damage to the TCU oil pump is caused by bearing damage due to lack of lubrication, shaft wear, damage to the couple and rubber couple, leaks in pipes and valves, leaks in the and pump mechanical seal. Various designs and configurations of centrifugal pumps have been carried out, both experimentally and in simulations with various configurations and variations. In short, this research will examine damage to the oil pump temperature control unit on longitudinal stretcher machines in terms of production cost losses at PT. POLYDAYAGUNA PERKASA Ungaran with a mathematical analysis approach. The research results show that the estimated loss in production costs due to damage to the TCU oil pump with within 6 months is IDR. 600,000,000,- and Rp. 120,000,000,- for pumps with mechanical seals. Estimated production cost losses for oil pumps with mechanical seals are highly recommended for use on longitudinal stretching machines because they are more efficient, but there must be further development.